Agronomic, physiological, and phytochemical responses of physalis to pre- and post-emergence herbicides - Gabardo, Anderson Luis Nunes (2025)
Cape gooseberry (Physalis peruviana L.) is a fruit crop with increasing economic and functional relevance, yet limited research exists on weed management practices for this species. This study aimed to evaluate the agronomic, physiological, and phytochemical responses of P. peruviana to various pre- and post-emergence herbicides under greenhouse and field conditions. Two biotypes were used to assess selectivity and crop tolerance to thirteen post-emergence and two pre-emergence herbicides. Post-emergence trials revealed that chlorimuron, fomesafen, and the mixture atrazine + simazine significantly reduced plant height and caused high phytotoxicity, especially under field conditions. Conversely, quizalofop, clethodim, fluazifop, and clodinafop (ACCase inhibitors) showed excellent selectivity and maintained yield levels comparable to the control. Pre-emergence applications of S-metolachlor exhibited minimal effects on plant growth and effectively reduced weed density, while imazaquin caused a dose-dependent reduction in plant height and yield, particularly in one biotype. Phenolic compound analysis indicated that both herbicide application and weed presence influenced fruit quality. Plants grown under weed-free conditions presented the highest total phenolic content, while high weed pressure or herbicide injury reduced phenolic accumulation, especially in biotype 2. The results demonstrate that while some herbicides pose risks to P. peruviana development, others offer promising weed control options with minimal impact on crop performance and fruit quality. These findings contribute to the development of safe and effective weed management strategies for this emerging crop.